HAMBATAN APLIKASI STANDAR AKUNTANSI KEUANGAN PADA KOPERASI WANITA SETIA BHAKTI WANITA SURABAYA - Kristianti, Anastasia Shinta (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research at Koperasi Wanita Setia Bhakti Wanita Surabaya is to evaluate whether the 2012 financial statement is in accordance with Financial Accounting Standard of Entities without Public Accountability (SAKETAP) and to analyze the relation between the presentation and recording of financial statement and cooperative law, and to analyze the existing problem in the implementation of financial accounting standard. The qualitative approach with case study method is used by researcher in the preparation of this thesis. The financial statements consist of balance sheet, the calculation of business result, summary of net assets position changes, cash flow statement, and record of financial statement. After the comparison has been carried out, the result is overall the financial accounting standard has been entirely implemented. However there are several financial statement account names which do not fit such as: the report of calculation of business result and the summary of net assets position changes. The presentation and recording of financial statement has close relationship to the cooperative law since it is the guideline of all activities in cooperation including the guideline which is applied by Indonesian Institute of Accountants (IAI) in the making and the determination of financial accounting standard. There are constraint in implementing this standard, cooperative objected when calculation of employee benefits in actuary. Keywords: Financial Accounting Standard of Entities without Public Accountability (SAKETAP), Cooperative Law, Financial Statement.